The effect of hydrogel particle size on water retention properties and availability under water stress - Abdallah, Ahmad M. (International Soil and Water Conservation Research, 2019)
The use of superabsorbent polymers or hydrogels could increase the water holding capacity (WHC) of sandy soil and reduce water loss by deep percolation. However, hydrogels' retained water availability to plants might be overestimated without taking into consideration the hydrogel particles size. Therefore, the ultimate objective of this study was to address the impacts of hydrogel particles size on hydrogel's retained water availability (plant available water, PAW), daily water consumption (DWC) and survival of Guava seedlings subjected to drought. Moreover, some soil physical properties, i.e., WHC, water retention properties, and hydraulic conductivity (Ksat) were investigated. Hydrogel (WaterSorb, “WS”) application, particularly the WS of small particles, significantly reduced Ksat, and increased WHC and PAW. Therefore, seedlings grown in soil amended with WS fine (0.8–1.0 mm), WS medium (1.0–2.0 mm) and WS large (2–4 mm) survived for 27.0 ± 1.3, 24.0 ± 1.1 and 17.0 ± 0.7 days, respectively, compared to 13.0 ± 1.0 days for the control. The water stored in the WS of large particles was less readily available for plant roots. Interestingly, hydrogels, had no effect on the DWC of the seedlings. Utilizing hydrogels as a soil amendment increases WHC, PAW, growth and survival of Guava seedlings, while the effect was less pronounced for the large hydrogel particles which had lower specific surface area and swelling rate.